Comparison of simple and economic DNA extraction methods for molecular diagnosis of leptospirosis in animals (FAVE Sección Ciencias Veterinarias, 2019)
Bovine leptospirosis is an important zoonotic disease whose molecular diagnosis is widely reported. However, there is not a unique method of extraction of DNA for pathogenic leptospires using clinical samples. In this study, bovine urine was contaminated with pure culture of L. interrogans serovar Pomona Pomona in order to compare three of them: M1.) resin Chelex-100, M2.) FTA Whatman paper and M3.) boiling of the sample (in house protocol), being the first one the most sensitive when used in diagnostic PCR, detecting up to 2x102 leptospiras/mL. The methodology proposed in this study turned out to have good performance for the detection of leptospires in animal clinical samples, although it should be applied to a greater number of samples and in different stages of the pathology.